Folliculin Interacts with Rab35 to Regulate EGF-Induced EGFR Degradation - Zheng, Jianchao; Duan, Biao; Sun, Shixiu; Cui, Jie; Du, Jun; Zhang, Yujie (Frontiers in Pharmacology, 2017)
Aims and hypothesis: This study aims to investigate the mechanism involved in intracellualr regulation of EGFR degradation induced by EGF Methods: Phosphorylation of proteins related to EGFR signaling was examined by western blot analysis. Activation, connection of Rab35 and interference with folliculin (FLCN) were assessed by pulldown, coimmunoprecipitation assays separately. The relationship between FLCN and cell growth was detected using gene overexpression and knock-down techniques. Results: FLCN, a tumor suppressor, reduces the rate of EGF-induced EGFR degradation, resulting in prolonged activation of downstream signaling. Rab35 activation is also required in these processes. Moreover, C-terminal of FLCN binds to and activates Rab35. Of special interest is the observation that erlotinib, a selective EGFR inhibitor, not only obstructs the EGFR-mediated cellular signaling, but also abolishes EGF-stimulated EGFR degradation. Further results reveal that EGF facilitates the activation of Rab35, and FLCN modulates EGF-dependent Rab35 activation and cell growth. Conclusions: Taken together, our study proposes a negative-feedback regulation model in which FLCN mediates EGF-induced Rab35 activation, thereby increasing EGFR degradation and attenuating EGFR signaling.